2001
DOI: 10.1182/blood.v97.10.3123
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of the urokinase-type plasminogen activator receptor by metalloproteinase-12: implication for angiogenesis in fibrin matrices

Abstract: IntroductionThe urokinase-type plasminogen activator (u-PA) and its cellular receptor (u-PAR, CD87) are involved in cell migration such as occurs during tumor invasion and angiogenesis. 1 The u-PAR regulates the u-PA activity on the cell surface not only by mediating the localization of u-PA and the internalization of u-PA/inhibitor complexes but also by an increase in the efficiency of plasminogen activation by u-PAR-bound u-PA. 2 Pro-u-PA bound to the receptor can be converted into the protease u-PA and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 63 publications
5
86
0
5
Order By: Relevance
“…Furthermore, MMP-9 could cleave the uPA-binding domain from uPAR in vitro. uPAR cleavage has also been observed on the cell surface, and this cleavage can be inhibited with a broad-spectrum MMP inhibitor BB-94 (Koolwijk et al, 2001). We found that a gelatinase-selective smallmolecule inhibitor and the CTT peptide inhibited the cellular cleavage of uPAR.…”
Section: Mmp-9 Interacts With the Urokinase-plasminogen Activator Recmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, MMP-9 could cleave the uPA-binding domain from uPAR in vitro. uPAR cleavage has also been observed on the cell surface, and this cleavage can be inhibited with a broad-spectrum MMP inhibitor BB-94 (Koolwijk et al, 2001). We found that a gelatinase-selective smallmolecule inhibitor and the CTT peptide inhibited the cellular cleavage of uPAR.…”
Section: Mmp-9 Interacts With the Urokinase-plasminogen Activator Recmentioning
confidence: 79%
“…This suggests that uPA and MMPs are activated prior to integrin activation and remain associated to the integrins. Furthermore, uPAR can be cleaved by uPA (Hoyer-Hansen et al, 1992) or MMPs in vitro (Andolfo et al, 2002;Koolwijk et al, 2001) and the cleaved uPAR form is also found in invasive tumor xenografts (Solberg et al, 1994). The cleavage occurs between domains 1 and 2 impairs uPA and integrin binding (Montuori et al, 2002) and exposes a chemotactic epitope (Fazioli et al, 1997) suggesting that this cleavage is one of the cell migration regulating events on the cell surface.…”
Section: Other Proteases In Cell Migration and Invasionmentioning
confidence: 99%
“…This report suggests that EC-derived MMP-12 may be involved in negative regulation of angiogenesis via uPAR shedding, perhaps providing a negative feedback mechanism to limit neovascularization. 123 However, another group has reported that treatment of mice with BB94 increased the levels of MMP-9 and MMP-2 in their livers. 124 In light of this report, the effects of BB94 on endothelial expression of MMPs will need to be tested, as it is possible that the proangiogenic effects of BB94 seen in the previous report 123 are due to increased MMP-9 and MMP-2 production (leading to enhanced activity when levels exceed that of the inhibitor) and not a result of MMP inhibition.…”
Section: The Modus Operandi Proangiogenic Activities Of Metalloproteimentioning
confidence: 99%
“…MMPs inhibit the process of angiogenesis by the following mechanism: i) By cleavage of plasminogen which releases angiostatin (Cornelius et al, 1998); ii) By cleaving collagen XVIII which produces endostatin (Ferreras, 2000); iii) By shedding of cell surface bound urokinase type plasminogen activator receptors which are required for the endothelial cell invasion in to fibrin (Koolwijk et al, 2001). …”
Section: Regulation Of Angiogenesismentioning
confidence: 99%